A thin film material and its preparation method and application

By preparing the modified membrane layer and controlling its hydrophilicity during vacuum suction filtration, the problem of the suction filtration membrane easily forms defects during peeling is solved, and the structural integrity and performance improvement of the film material is achieved. It is suitable for Preparation of a variety of high-performance materials.

CN117547977BActive Publication Date: 2025-02-18CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311719621.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-14
Publication Date
2025-02-18
Estimated Expiration
2043-12-14

AI Technical Summary

Technical Problem

In the existing vacuum suction filter membrane production method, the suction filter membrane is prone to form uneven and discontinuous structures such as wrinkles, cracks, and damage during the peeling process, resulting in poor performance of the film material.

Method used

By preparing a modified membrane layer between the base membrane and the suction filter membrane, the redox active nanomaterial reacts with a reducing agent or a silane coupling agent to regulate the hydrophilicity and binding energy of the modified membrane layer, so that the suction filter membrane and the suction filter membrane are combined with the The adhesion force of the modified film layer is smaller than the adhesion force between the modified film layer and the base film, thereby achieving smooth peeling and transfer of the suction filter membrane to the substrate material.

Benefits of technology

The structural integrity and performance of the suction filter membrane are improved, and a broken and wrinkle-free film material is obtained, which is suitable for the preparation of thermally controlled composite materials with gradient thermal conductivity and stretchable flexible sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117547977B_ABST
    Figure CN117547977B_ABST
Patent Text Reader

Abstract

The present invention relates to a thin film material and a preparation method and application thereof, belonging to the technical field of thin film material preparation. The preparation method of the thin film material comprises dispersing a redox-active nano material, adding a reducing agent or a silane coupling agent, heating at 35-50°C and stirring the reaction to obtain a modified film layer liquid; mixing powder particles with a dispersant to obtain a filtrate; placing a hydrophilic bottom membrane in a filtration device, pouring the modified film layer liquid into the filtration device, and forming a modified film layer on the bottom membrane after filtration; then pouring the filtrate into the filtration device, drying, and obtaining a composite film layer, wherein the composite film layer is a bottom membrane, a modified film layer and a filtration membrane in sequence; laminating the filtration membrane on a substrate material, and then dripping water on the side of the substrate membrane away from the modified film layer to obtain a thin film material composed of the substrate material and the filtration membrane, thereby obtaining a thin film material with a complete structure and high performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thin film material preparation, and in particular to a thin film material and a preparation method and application thereof. Background Art

[0002] Vacuum filtration membrane technology is widely adopted in the film formation process of various powders and two-dimensional nanomaterials. It has the advantages of simple operation, adjustable membrane thickness and low cost. The prepared filtration membrane is also widely used in thermal control, flexible sensing and other fields after being combined with the substrate material.

[0003] The vacuum filtration film making method needs to peel off the suction filtration membrane and the base film, and then transfer to the substrate material to obtain the film material. Existing stripping methods mainly adopt solvent stripping (also referred to as wet stripping), mechanical stripping and thermal stripping. Solvent stripping uses water or chemical solvent to decompose or soften the bonding force between the suction filtration membrane and the base film, and makes the suction filtration membrane peel off, and then adheres to the target substrate with smooth surface. However, the surface of the suction filtration membrane prepared by this method often forms uneven and discontinuous structures such as wrinkles, cracks, and damage, which directly affects the subsequent use and the performance of the film material. Mechanical stripping, i.e. manual tearing or using tools (such as scrapers, scissors, etc.) to peel off, this method is only applicable to thicker or more solid suction filtration membranes, and is easy to cause the damage of the suction filtration membrane. Thermal stripping, i.e. heating the suction filtration membrane and the base film to achieve the purpose of softening or melting the base film, so that the suction filtration membrane is separated from the base film, and this method is easy to cause irreparable pollution to the suction filtration membrane material, and its structure and performance impact are also relatively large.

[0004] Therefore, there is an urgent need for a method for preparing a thin film material, which can separate the filtration membrane from the base membrane and transfer the complete and high-quality filtration membrane to the substrate material to obtain a damage-free and wrinkle-free thin film material. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a thin film material and a preparation method and application thereof, so as to solve the problem that it is currently impossible to obtain a thin film material with a perfect shape.

[0006] In one aspect, the present invention provides a method for preparing a thin film material, comprising the following steps:

[0007] S1: dispersing the redox-active nanomaterial, then adding a reducing agent or a silane coupling agent, heating at 35-50°C and stirring for reaction, to obtain a modified membrane layer liquid;

[0008] S2: mixing the powder particles with a dispersant to obtain a filtrate; wherein the powder particles are selected from ceramic powder, ceramic short fibers, adhesives and two-dimensional nanomaterials;

[0009] S3: placing a hydrophilic bottom membrane in a suction filtration device, pouring the modified membrane layer liquid into the suction filtration device, and forming a modified membrane layer on the bottom membrane after suction filtration; then pouring the filtrate into the suction filtration device, and after drying, obtaining a composite membrane layer, wherein the composite membrane layer is the bottom membrane, the modified membrane layer and the suction filtration membrane in sequence;

[0010] S4: Laminating the suction filtration membrane on the substrate material, and then dripping water on the side of the substrate away from the modified membrane layer to obtain a thin film material composed of the substrate material and the suction filtration membrane.

[0011] Furthermore, the substrate material is selected from ceramics, glass, silicon wafer, plastic, polydimethylsiloxane film, polymethyl methacrylate film and polyvinylidene fluoride film.

[0012] Furthermore, the thickness of the filtration membrane is ≤1 mm, and the thickness of the substrate material is ≤3 mm.

[0013] Furthermore, the redox active nanomaterial comprises at least one of a two-dimensional nanomaterial having redox activity and a nanomaterial carrying redox active heteroatoms.

[0014] Furthermore, the two-dimensional nanomaterial having redox activity includes graphene oxide.

[0015] Furthermore, the silane coupling agent is selected from vinyltrimethoxysilane, 3-propylmethyldimethylsilane and γ-propyltrimethoxysilane.

[0016] Furthermore, the mass ratio of the redox active nanomaterial to the silane coupling agent is 1:(0.05-0.5).

[0017] Furthermore, the adhesive is one or more of water glass, magnesium oxide powder, yttrium oxide powder and aluminum oxide powder.

[0018] Furthermore, the two-dimensional nanomaterial is one or more of graphene, reduced graphene oxide (rGO), MXene, hexagonal boron nitride and molybdenum disulfide.

[0019] In another aspect, the present invention provides a thin film material obtained by the method for preparing the thin film material of the present invention, wherein the thin film material is composed of a substrate material and a filtration membrane. The thin film material is used to prepare a thermal control composite material with gradient thermal conductivity and a stretchable flexible sensor.

[0020] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0021] 1. The present invention provides a method for preparing a thin film material, wherein a modified film layer is added between a base film and a filtration membrane to separate the base film from the filtration membrane, so that the bonding force between the filtration membrane and the modified film layer is smaller than the bonding force between the modified film layer and the base film, thereby achieving peeling of the filtration membrane, and then transferring the filtration membrane with higher structural integrity to a substrate material, thereby obtaining a thin film material with complete structure and higher performance.

[0022] 2. In the process of stripping the filtration membrane, the present invention adds a reducing agent or a silane coupling agent to the nanomaterial with redox activity, so that the nanomaterial with redox activity is partially reduced or reacts with the silane coupling agent, and the number and state of the functional groups on the surface of the nanomaterial with redox activity are regulated, thereby being able to regulate the hydrophilicity, surface tension or binding energy of the modified film layer, and regulating the adhesion or binding energy between the modified film layer and the filtration membrane to be less than the adhesion or binding energy between the modified film layer and the base film, thereby facilitating the stripping of the filtration membrane and the base film and transferring them to the substrate material.

[0023] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0025] Figure 1 Schematic diagram of the reduced graphene oxide / polydimethylsiloxane (PDMS) composite film material in Example 1;

[0026] Figure 2 Schematic diagram of the hexagonal boron nitride / polymethyl methacrylate (PMMA) composite film material in Example 2;

[0027] Figure 3 Schematic diagram of the damage of the hexagonal boron nitride thin film filter material during the transfer process to the substrate in Comparative Example 1;

[0028] Figure 4 This is a schematic diagram of transferring the reduced graphene oxide filtration membrane to the substrate silicon wafer by the common wet method in Comparative Example 2;

[0029] Figure 5 Schematic diagram of cutting the composite film composed of filtration membrane / substrate material to prepare a flexible stretchable sensor;

[0030] Figure 6Schematic diagram of the mechanoelectric response performance of the reduced graphene oxide / PDMS composite film-based flexible stretchable sensor at a strain frequency of 5 Hz. DETAILED DESCRIPTION

[0031] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0032] Vacuum filtration is one of the commonly used methods in membrane preparation. In order to obtain thin film materials, the filtration membrane needs to be peeled off from the base film and then transferred to the substrate material. In the process of transferring the filtration membrane, solvent peeling, mechanical peeling and thermal peeling are mainly used. However, when peeling off the base film and the filtration membrane, the obtained filtration membrane has defects such as wrinkles, cracks, and damage, and its integrity is poor. Therefore, the obtained thin film material is also incomplete, which affects its performance.

[0033] Therefore, a method for preparing a thin film material comprises the following steps:

[0034] S1: dispersing the redox-active nanomaterial, then adding a reducing agent or a silane coupling agent, heating at 35-50°C and stirring for reaction, to obtain a modified membrane layer liquid;

[0035] S2: mixing the powder particles with a dispersant to obtain a filtrate; wherein the powder particles are selected from ceramic powder, ceramic short fibers, adhesives and two-dimensional nanomaterials;

[0036] S3: placing a hydrophilic bottom membrane in a suction filtration device, pouring the modified membrane layer liquid into the suction filtration device, and forming a modified membrane layer on the bottom membrane after suction filtration; then pouring the filtrate into the suction filtration device, and after drying, obtaining a composite membrane layer, wherein the composite membrane layer is the bottom membrane, the modified membrane layer and the suction filtration membrane in sequence;

[0037] S4: Laminating the suction filtration membrane on the substrate material, and then dripping water on the side of the substrate away from the modified membrane layer to obtain a thin film material composed of the substrate material and the suction filtration membrane.

[0038] Compared with the prior art, the method for preparing a thin film material provided by the present invention prepares a modified film layer between a base film and a suction filtration membrane, and the modified film layer is dispersed with a redox-active nanomaterial and then a reducing agent or a silane coupling agent is added, so that the redox-active nanomaterial is partially reduced or reacts with the silane coupling agent, and the number and state of the functional groups on the surface of the redox-active nanomaterial are regulated, thereby regulating the hydrophilicity, surface tension or binding energy of the modified film layer. After adding the reducing agent or the silane coupling agent, the bonding force between the suction filtration membrane and the modified film layer is smaller than the bonding force between the modified film layer and the base film, so that the suction filtration membrane and the base film and the modified film layer are peeled off, and a suction filtration membrane with high structural integrity is obtained; and then the suction filtration membrane is transferred to the substrate material, and finally a thin film material with complete structure and high performance is obtained.

[0039] Specifically, in step S1, the redox-active nanomaterial includes at least one of a two-dimensional nanomaterial having redox activity and a nanomaterial carrying redox-active heteroatoms;

[0040] Preferably, the two-dimensional nanomaterial with redox activity includes graphene oxide (represented by GO) and MOF material with redox activity.

[0041] Preferably, the nanomaterial loaded with redox active heteroatoms includes carbon nanosheets loaded with redox active heteroatoms, transition metal oxide nanosheet materials, such as oxidized Ti3C2Tx nanosheets modified with epoxy functional groups.

[0042] Specifically, the redox active nanomaterial and the powder particles are dispersed in a dispersion liquid, and the dispersion liquid can be water or a mixed solution of water and an organic solvent, and the volume content of the organic solvent is preferably 0% to 50%.

[0043] Preferably, the organic solvent includes one or more of methanol, ethanol, isopropanol, isopentanol, propargyl alcohol, dimethylformamide, acetone, and tetrahydrofuran.

[0044] Specifically, the reducing agent is selected from vitamin C, hydroiodic acid, hydrazine hydrate and ethyl acetate.

[0045] Preferably, the mass ratio of the redox active nanomaterial to the reducing agent is 1:(0.01-2).

[0046] When preparing the modified membrane layer liquid, a reducing agent or a silane coupling agent needs to be added. The addition of the reducing agent or the silane coupling agent is used to adjust the number and state of the redox active functional groups on the surface of the modified membrane layer, so as to adjust the hydrophilicity and binding energy of the modified membrane layer. Adding a reducing agent or a silane coupling agent to the modified membrane layer can, on the one hand, enhance the mechanical strength of the modified membrane layer itself, and prevent the modified membrane layer from being damaged and adhering to the suction filtration membrane when peeling; on the other hand, by regulating the epoxy functional groups in the modified membrane layer by the reducing agent or the silane coupling agent, the binding energy between the modified membrane layer and the suction filtration membrane can be reduced; at the same time, the modified membrane layer swells after absorbing water. As the amount of water gradually increases, the electrostatic repulsion on the modified membrane layer unit will promote the collapse of the modified membrane layer structure by dripping water on the bottom membrane, thereby reducing the binding force between the modified membrane layer and the suction filtration membrane, and then separating the suction filtration membrane from the modified membrane layer.

[0047] The binding energy or binding force between the base membrane and the modified membrane layer is higher than the binding energy or binding force between the filtration membrane and the modified membrane layer. When water is added, the modified membrane layer absorbs water and swells, but the binding energy or binding force between the base membrane and the modified membrane layer is still higher than the binding energy or binding force between the filtration membrane and the modified membrane layer, and the binding energy between the filtration membrane and the substrate material is relatively high. Therefore, the filtration membrane can be smoothly peeled off from the modified membrane layer and smoothly transferred to the substrate material to obtain a complete thin film material.

[0048] When a reducing agent is used for regulation, the pH value of the modified membrane layer liquid is determined by the type of the reducing agent, and the pH value range of the modified membrane layer liquid is 4-6 (such as adding HI or vitamin C) or 8-11 (such as adding hydrazine hydrate and ammonia water).

[0049] When a silane coupling agent is used for regulation, specifically, the silane coupling agent is selected from vinyltrimethoxysilane, 3-propylmethyldimethylsilane and γ-propyltrimethoxysilane.

[0050] Preferably, the mass ratio of the redox active nanomaterial to the silane coupling agent is 1:(0.05-0.5).

[0051] When preparing the modified membrane layer liquid, a silane coupling agent needs to be added. The addition of the silane coupling agent is also to regulate the number and state of the redox-active surface functional groups, so as to achieve the regulation of its hydrophilicity and surface binding energy. When adding the silane coupling agent, the pH value needs to be adjusted to be acidic or alkaline. The pH value range is 4 to 6 or 8 to 10, which can react with the surface functional groups in the redox-active nanomaterials, thereby regulating the number and state of the redox-active surface functional groups.

[0052] Generally speaking, the surface energy of the filtration membrane and the base membrane is relatively high, and the filtration membrane and the base membrane are not easy to peel off. When preparing the thin film material of the present invention, firstly a modified film layer is prepared on the base membrane, and then the filtration membrane is covered on the modified film layer, and a composite film layer is obtained after drying; the composite film layer is placed on the substrate material, wherein the filtration membrane is in contact with the substrate material; finally, deionized water is dripped on the base membrane, and as the modified film layer swells, the interfacial adhesion or binding energy between the modified film layer and the filtration membrane will also decrease rapidly. At this time, the binding energy between the base membrane and the modified film layer is higher than the binding energy between the filtration membrane and the modified film layer, and the filtration membrane is peeled off from the composite film layer. Moreover, the binding energy between the substrate material and the filtration membrane is much greater than the binding energy between the filtration membrane and the modified film layer, and the filtration membrane is directly transferred to the substrate material to obtain a complete thin film material.

[0053] Specifically, the heating temperature is 35-50°C.

[0054] When preparing the modified film layer, a reducing agent or the silane coupling agent is added to the redox-active nanomaterial. After heating reaction, the redox-active nanomaterial and the reducing agent or the silane coupling agent are more likely to react, thereby regulating the content and state of the surface functional groups of the redox-active nanomaterial. When the temperature is lower than 35°C, the number of surface functional groups in the modified film layer is relatively large. In the case of water absorption, the modified film layer has no mechanical strength and can even be completely dissolved and dispersed in water; when the temperature is higher than 50°C or even higher, the number of surface functional groups in the modified film layer is relatively small, and its structural stability is relatively high. After the modified film layer absorbs water, the adhesion between it and the filtration membrane will not be reduced, so it cannot be smoothly peeled off and transferred.

[0055] Specifically, the powder particles are one or more of ceramic powder, ceramic short fibers, adhesives and two-dimensional nanomaterials.

[0056] Preferably, the ceramic powder is selected from oxide ceramics, nitride ceramics, carbide ceramics and silicide ceramic powders.

[0057] More preferably, the particle size of the ceramic powder is 0.5 to 500 microns.

[0058] Preferably, the ceramic short fibers are selected from glass fibers, oxide ceramic fibers, nitride ceramic fibers, and ceramic nanorods.

[0059] Preferably, the adhesive is one or more of water glass, magnesium oxide powder, yttrium oxide powder and aluminum oxide powder.

[0060] Preferably, the two-dimensional nanomaterial is one or more of graphene, reduced graphene oxide, MXene, hexagonal boron nitride and molybdenum disulfide.

[0061] In step S3, vacuum filtration technology is mainly used to form a layered composite membrane layer, which is a base membrane, a modified membrane layer and a filtration membrane in sequence. By adjusting the hydrophilicity and surface tension of the modified membrane layer, the bonding force between the base membrane and the modified membrane layer is made greater than the bonding force between the modified membrane layer and the filtration membrane, which facilitates the peeling of the filtration membrane from the base membrane, and obtains a filtration membrane with a complete structure, which can then be transferred subsequently.

[0062] Specifically, the bottom membrane is a hydrophilic filter membrane.

[0063] Preferably, the hydrophilic filter membrane is selected from cellulose filter membrane, alumina filter membrane, nylon filter membrane, vinylidene fluoride filter membrane and polytetrafluoroethylene filter membrane.

[0064] Preferably, the size of the base film is 47 mm or 50 mm, and the pore size is 0.15 μm-0.8 μm.

[0065] In the present invention, the function of the hydrophilic filter membrane is to enable the modified membrane layer and the suction filtration membrane to complete the suction filtration smoothly; and when the suction filtration membrane and the modified membrane layer are peeled off, water can penetrate into the modified membrane layer in time.

[0066] Specifically, the substrate material is selected from ceramics, glass, silicon wafer, plastic, polydimethylsiloxane film, polymethyl methacrylate film and polyvinylidene fluoride film.

[0067] In the present invention, the substrate material is used to receive the filtration membrane and form a new film material with the filtration membrane. The thickness of the filtration membrane is ≤1mm, and the thickness of the substrate material is ≤3mm. The thermal conductivity of the substrate material is low, relatively stable, and has good deformation performance. In the application scenario of a local heated environment, the obtained film material will not cause problems such as cracking and failure of the film material due to stress concentration, and will not cause damage to the filtration membrane. Therefore, the film material is used to prepare thermal control composite materials with gradient thermal conductivity, stretchable flexible sensors, etc.

[0068] In order to more clearly describe the present invention, it is further illustrated by the following examples and comparative examples.

[0069] Example 1

[0070] A method for preparing a thin film material comprises the following steps:

[0071] S1: 10 μg of a redox-active nanomaterial is dispersed in a mixed solution of 5 ml of water and methanol, and then 0.5 μL of a reducing agent N2H4 (density 1.032 mg / ml) with a mass percentage of 30 wt.%, i.e., the mass ratio of the redox-active nanomaterial to the reducing agent is about 1:0.015, and the mixture is reduced at a constant temperature of 35° C. with stirring for 10 minutes to obtain a modified membrane layer liquid;

[0072] The redox-active nanomaterial is graphene oxide (GO).

[0073] S2: Disperse 20 mg of reduced graphene oxide (with a carbon content of more than 70 wt%) in 5 ml of water and stir at a constant temperature for 1 hour to prepare a reduced graphene oxide filtrate;

[0074] S3: Using vacuum filtration technology, a vacuum filtration device is built, a cellulose filter membrane is selected as a bottom membrane (47 mm, 0.22 μm pore size), the modified membrane layer liquid is poured into the Buchner funnel of the filtration device, and after the filtration is completed, the filtrate is poured into the filtrate, and after drying, a cellulose filter membrane layer / semi-reduced graphene oxide layer / reduced graphene oxide composite membrane layer is obtained, which is the bottom membrane layer, the modified membrane layer and the filtration membrane layer in sequence;

[0075] S4: The filtration membrane on the composite membrane layer is laminated onto the substrate material. The filtration membrane layer is laminated onto the substrate material. 0.5 ml of deionized water is dripped on the back of the cellulose filter membrane (bottom membrane layer). After infiltration, the filtration membrane can be directly peeled off from the surface of the modified membrane / bottom membrane composite membrane and transferred to the substrate material (made of polydimethylsiloxane membrane, i.e., PDMS membrane). The thickness of the PDMS membrane is about 3 mm. The surface is treated with oxygen plasma for 2 minutes (power 200 W) to obtain a completely reduced graphene oxide / PDMS composite thin film material.

[0076] Example 2

[0077] A method for preparing a thin film material comprises the following steps:

[0078] S1: Disperse 20 mg GO evenly in 5 ml aqueous solution, take 10 mg silane coupling agent and add it to 5 ml anhydrous ethanol, mix the GO dispersion with the silane coupling agent solution, ultrasonicate for 30 min, add hydrochloric acid to the mixed solution to adjust the pH of the solution to 4-5, place the mixed solution in a 50°C water bath for reaction for 30 minutes and then cool to room temperature, then centrifuge and wash several times to remove the unreacted silane coupling agent, and adjust the solution pH to 6-7. Add a mixture of water and anhydrous ethanol (anhydrous ethanol accounts for 25% by volume) and dilute it 100 times, and use it as a modified membrane layer liquid for later use;

[0079] S2: 9 mL of 17.5 mg / ml hexagonal boron nitride isopropanol dispersion was mixed with 15.75 mg of ceramic powder, which was a mixed powder of Al2O3 fiber powder (particle size ~0.5 μm, purity>99%) and MgO (particle size ~1 μm, purity>99%) (the mass ratio of Al2O3 to MgO was 3:2), and mechanically stirred at room temperature for 15 min, and used as the filtrate for standby use;

[0080] S3: Build a vacuum filtration device, select an alumina filter membrane as a base membrane (47 mm, 0.2 μm pore size), first pour the modified membrane layer liquid into the filtration device, and after the filtration is completed, pour the filtrate into it until it is completely dry, to obtain an alumina filter membrane / silane coupling agent modified graphene oxide membrane / hexagonal boron nitride composite membrane layer, which is the base membrane layer, the modified membrane layer and the filtration membrane layer in sequence;

[0081] S4: Lay the filtration membrane on the composite membrane layer on the substrate material, and the filtration membrane layer and the substrate material are laminated. The composite membrane layer and the substrate material are cut to the same shape. After dripping water (0.3 ml) on the back of the alumina filter membrane (bottom membrane layer), the composite membrane of the bottom membrane layer and the modified membrane layer is removed and transferred to the substrate material (made of polymethyl methacrylate film, i.e. PMMA film). The thickness of the PMMA film is 750 μm, and finally the hexagonal boron nitride / PMMA composite film material is obtained.

[0082] Example 3

[0083] A method for preparing a thin film material comprises the following steps:

[0084] S1: 50 μg of oxidized Ti3C2T modified with epoxy functional groups was added x The nanosheets were evenly dispersed in 5 ml of deionized water solution, ultrasonicated for 15 min, 0.05 μL of HI solution (density 1.941 g / ml) was added, i.e., the mass ratio of the redox active nanomaterial to the reducing agent was about 1:1.941, and reduced at 35° C. with constant temperature stirring for 10 min, and used as a modified membrane layer liquid for later use;

[0085] S2: Weigh 30 mg of reduced graphene oxide (carbon content greater than 70 wt%) aqueous dispersion in a glass container (reduced graphene oxide flake size is 5-10 μm), stir thoroughly and freeze in dry ice for 30 min, then freeze-dry under vacuum low temperature conditions to obtain a structurally complete reduced graphene oxide porous block material; weigh 25.4 mg FeCl3·6H2O was dissolved in 3 ml of deionized water and stirred thoroughly until it was completely dissolved, and the reduced graphene oxide porous block material was completely immersed in the FeCl3 solution and immersed at room temperature for 12 hours to obtain a mixed solution; 0.2 ml of a 35% mass fraction N2H4 aqueous solution (density of 1.032 mg / ml) was weighed and added to the obtained mixed solution to obtain a composite solution, and then the composite solution was placed in an oven for wet chemical reduction reaction at a reaction temperature of 35°C for 24 hours; after naturally cooling to room temperature, the reaction solution was fully replaced and washed with deionized water, ultrasonicated and stirred, and the reduced graphene oxide porous block material was crushed and dispersed in the mixed solution, diluted 100 times, and used as a suction filtration membrane for standby;

[0086] S3: Build a vacuum filtration device, select nylon filter membrane as the bottom membrane material (47 mm, 0.2 μm pore size), pour the modified membrane layer liquid into the Buchner funnel of the filtration device, pour the filtrate after filtration, and dry it to obtain nylon filter membrane / semi-reduced oxidized Ti3C2T x / transition metal loaded reduced graphene oxide composite membrane layer, which is a base membrane layer, a modified membrane layer and a filtration membrane layer in sequence;

[0087] S4: The filtration membrane on the composite membrane layer is laminated onto the substrate material. The filtration membrane layer is laminated onto the substrate material. 0.3 ml of deionized water is dripped on the back of the nylon filter membrane (bottom membrane layer). After infiltration, the filtration membrane can be directly peeled off from the surface of the modified membrane layer / bottom membrane composite layer and transferred to the substrate material (made of glass sheet). The thickness of the glass sheet is about 1.7 mm. The surface is treated with oxygen plasma for 10 minutes (power 200 W) to finally obtain a complete transition metal-loaded reduced graphene oxide membrane / glass composite thin film material.

[0088] Comparative Example 1

[0089] A method for preparing a thin film material comprises the following steps:

[0090] S1: 9 mL of 17.5 mg / ml hexagonal boron nitride isopropanol dispersion was mixed with 15.75 mg of mixed powder of Al2O3 and MgO (the mass ratio of Al2O3 to MgO was 3:2), and mechanically stirred at room temperature for 15 min, and used as the filtrate for standby use;

[0091] S2: Build a vacuum filtration device, select an alumina filter membrane as the base membrane (47 mm, 0.2 μm pore size), first pour the modified membrane layer liquid into the filtration device, and then pour the filtrate into the filtration device after filtration is completed. After it is completely dry, tear it directly off from the base membrane. The filtration membrane is damaged and cannot be transferred.

[0092] Comparative Example 2

[0093] A method for preparing a thin film material comprises the following steps:

[0094] S1: 25 ml of 0.05 mg / ml reduced graphene oxide solution (carbon content higher than 70 wt%), reduced graphene oxide flake size of about 5 μm), 1.8 ml of NH3·H2O, and 0.625 ml of 30 wt.% N2H4 were mixed and reduced at 90°C with constant temperature stirring for 1 hour to prepare a filtrate;

[0095] S2: Use vacuum filtration technology to build a vacuum filtration device, select a cellulose filter membrane as the base membrane (47 mm, 0.22 μm pore size), pour the filtration membrane layer liquid into the Buchner funnel of the filtration device, pour the filtrate after filtration, and obtain the reduced graphene oxide / cellulose membrane composite membrane layer after drying.

[0096] S3: Cut the composite film layer to a size close to that of the substrate material and immerse it in deionized water until the reduced graphene oxide (filtration membrane) is separated from the bottom membrane. Use the substrate material (made of silicon wafer, 300 μm thick) to contact the reduced graphene oxide film with one side of the silicon wafer, laminate it, salvage it, and dry it to obtain a reduced graphene oxide film / silicon wafer composite film material.

[0097] Comparative Example 3

[0098] S1: 10 μg of a redox-active nanomaterial is dispersed in a mixed solution of 5 ml of water and methanol, and then 0.5 μL of a reducing agent N2H4 (density 1.032 mg / ml) with a mass percentage of 30 wt.%, that is, the mass ratio of the redox-active nanomaterial to the reducing agent is about 1:0.015, and the mixture is reduced at a constant temperature of 90° C. for 1 hour with stirring to obtain a modified membrane layer liquid;

[0099] S2: Disperse 20 mg of reduced graphene oxide (with a carbon content of more than 70 wt%) in 5 ml of water and stir at a constant temperature for 1 hour to prepare a reduced graphene oxide filtrate;

[0100] S3: Use vacuum filtration technology to build a vacuum filtration device, select cellulose filter membrane as the base membrane (47 mm, 0.22 μm pore size), pour the modified membrane layer liquid into the Büchner funnel of the filtration device, pour the filtrate after filtration, and after drying, obtain a cellulose filter membrane layer / semi-reduced graphene oxide layer / reduced graphene oxide composite membrane layer, which is the base membrane layer, modified membrane layer and filtration membrane in sequence.

[0101] 0.5 ml of deionized water was dripped on the back of the cellulose filter membrane. After infiltration, the modified membrane layer could not be clearly distinguished from the filtration membrane due to excessive reduction, nor could it be separated from the base membrane. In other words, a filtration membrane of completely reduced graphene oxide thin film material could not be obtained, and therefore transfer was impossible.

[0102] Performance Testing

[0103] The composite membranes obtained in the above-mentioned Examples 1-3 and Comparative Example 3 were tested, mainly testing the binding energy between the filtration membrane and the modified membrane layer, the modified membrane layer and the base membrane before and after the addition of water, and the binding energy between the filtration membrane and the base membrane in Comparative Example 1-2. The test results are shown in Table 1.

[0104] The Dataphysics Model OCA20 contact angle test analyzer was selected to analyze and measure the contact angles of different membrane materials with 15 μL of standard solution at 20°C. The standard solution was deionized water and diiodomethane. The equipment software package can analyze the surface tension of the liquid on different materials and analyze the binding energy.

[0105] Table 1 Test results (unit: mJ / m 2 )

[0106]

[0107] *In Table 1, “—” means not involved.

[0108] Macrostructure observation

[0109] Reference Figure 1-4 By comparing and observing the thin film materials obtained in the above-mentioned embodiments 1-3 and comparative examples 1-2, it can be clearly seen that after adding the modified film layer, embodiments 1-3 of the present invention can ensure that the filtration membrane can be smoothly peeled off from the base film and transferred to the substrate material, which not only ensures the integrity of the filtration membrane, but also ensures the performance of the thin film material.

[0110] Reference Figure 3 In comparative example 1, when no modified membrane layer is added, the filtration membrane and even the bottom membrane will be obviously torn when the filtration membrane and the bottom membrane are mechanically peeled off, and it is extremely difficult to obtain a filtration membrane / bottom membrane thin film material with a complete structure.

[0111] Reference Figure 4 In comparative example 2, when no modified film layer is added, when the filtration membrane and the base film are wet-peeled and transferred, although a relatively complete peeled filtration membrane layer can be obtained, the surface of the filtration membrane / base material composite film material after transfer and drying has obvious wrinkles, and the structure of the obtained film material is uneven, which affects the performance and usability of the film material.

[0112] Application Example 1

[0113] The composite film material obtained in Example 1 was Figure 5 The display steps can be used to produce flexible and stretchable conductive materials for the development of flexible and stretchable sensors.

[0114] Specifically, after the reduced graphene oxide film is transferred to the PDMS film to obtain the reduced graphene oxide / PDMS composite film, it is cut (the PDMS size is 30*8mm), the reduced graphene oxide film is centered, and silver paste and conductive are added to both ends of the reduced graphene oxide film to obtain a flexible and stretchable conductive composite film material.

[0115] Figure 6 The flexible and stretchable conductive composite film material prepared in Example 1 has good electromechanical response performance. During the cyclic stretching process, the flexible and stretchable reduced graphene oxide / PDMS composite film can exhibit an electrical signal change trend and range that matches the strain.

[0116] Application Example 2

[0117] The composite film material obtained in Example 2 has gradient thermal conductivity and heat resistance. Table 1 shows the thermal conductivity and heat resistance of different layers of the hexagonal boron nitride / PMMA composite film material. The thickness of hexagonal boron nitride is 110μm, and the thickness of PMMA is 300μm. Generally speaking, the thermal conductivity of PMMA is extremely poor. When it is locally heated, due to its low temperature bearing capacity (thermal deformation occurs at 90°C, softening and structural failure occurs at 110°C, and decomposition occurs at 200°C), its service life and temperature bearing capacity are limited in actual use. The hexagonal boron nitride / PMMA composite film material can optimize the thermal conductivity and temperature resistance of PMMA to a certain extent, expand its temperature bearing range (when the heated surface is at one end of the BN surface), and extend its service life to a certain extent.

[0118] Table 2 Thermal conductivity and heat resistance of hexagonal boron nitride / PMMA composite film materials

[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a thin film material, characterized in that: The following steps are involved: S1: Dispersing the redox-active nanomaterials, then adding a reducing agent or a silane coupling agent, heating at 35-50°C and stirring for reaction, to obtain a modified membrane layer liquid; S2: mixing the powder particles with a dispersant to obtain a filtrate; wherein the powder particles are selected from ceramic powder, ceramic short fibers, adhesives and two-dimensional nanomaterials; The adhesive is one or more of water glass, magnesium oxide powder, yttrium oxide powder and aluminum oxide powder; S3: placing a hydrophilic bottom membrane in a suction filtration device, pouring the modified membrane layer liquid into the suction filtration device, and forming a modified membrane layer on the bottom membrane after suction filtration; then pouring the obtained filtrate into the suction filtration device, and after drying, obtaining a composite membrane layer, wherein the composite membrane layer is a bottom membrane, a modified membrane layer and a suction filtration membrane in sequence; adding a modified membrane layer between the bottom membrane and the suction filtration membrane, separating the bottom membrane from the suction filtration membrane, so that the bonding force between the suction filtration membrane and the modified membrane layer is smaller than the bonding force between the modified membrane layer and the bottom membrane; S4: Laminating the suction filtration membrane on the substrate material, and then dripping water on the side of the substrate away from the modified membrane layer to obtain a thin film material composed of the substrate material and the suction filtration membrane.

2. The method for preparing the thin film material according to claim 1, characterized in that: The substrate material is selected from ceramics, glass, silicon wafer, plastic, polydimethylsiloxane film, polymethyl methacrylate film and polyvinylidene fluoride film.

3. The method for preparing the thin film material according to claim 1, characterized in that: The thickness of the filtration membrane is ≤1 mm, and the thickness of the substrate material is ≤3 mm.

4. The method for preparing the thin film material according to claim 1, characterized in that: The redox active nanomaterial comprises at least one of a two-dimensional nanomaterial having redox activity and a nanomaterial carrying redox active heteroatoms.

5. The method for preparing the thin film material according to claim 4, characterized in that: The two-dimensional nanomaterial with redox activity includes graphene oxide.

6. The method for preparing the thin film material according to claim 1, characterized in that: The silane coupling agent is selected from vinyltrimethoxysilane, 3-propylmethyldimethylsilane and γ-propyltrimethoxysilane.

7. The method for preparing the thin film material according to claim 1, characterized in that: The mass ratio of the redox active nanomaterial to the silane coupling agent is 1:(0.05-0.5).

8. The method for preparing a thin film material according to claim 1, characterized in that: The two-dimensional nanomaterial is one or more of graphene, reduced graphene oxide (rGO), MXene, hexagonal boron nitride and molybdenum disulfide.

Citation Information

Patent Citations

  • Preparation method and application of porous graphene / Ti3C2TX composite film material for ultra-fast electrochemical capacitor

    CN114655950A